Preventive detention in German criminal law. (2nd January 2016) - Kaspar, Johannes
Abstract : The German system of criminal sanctions is considered to contain a twin-track model with two clearly different groups of sanctions: classical criminal punishment on the one hand and measures of correction and prevention (Maßregeln der Besserung und Sicherung) on the other. Whereas the former are (mainly) based on the theory of retribution and atonement of guilt for a crime in the past, the latter only serve the purpose of preventing future crimes. This classical view, however, does not quite fit to modern penal theories stressing that also criminal punishment does have preventive functions and cannot be legitimized by referring to rather metaphysical principles like retribution or guilt atonement alone. With respect to the controversial measure of preventive detention (Sicherungsverwahrung) that was the issue of current verdicts of the European Court of Human Rights and the German Constitutional Court, the author argues that the picture of two separate tracks is therefore misleading. In his opinion, preventive detention should for several reasons be seen as a sanction at least very similar to a prison sentence. Like a regular custodial sentence (and unlike other stationary measures like custody in a psychiatric hospital), preventive detention is the consequence of a criminal act committed by a fully culpable offender. Its character as a measure that comes with a grave deprivation of liberty for this reason is very similar to a regular prison sentence; according to the author, the new guidelines by the German Constitutional Court considering the modalities of the execution of preventive detention the emphasis on more therapy and other rehabilitative efforts) are positive, but not apt to create a fundamental difference or "gap" between both sanctions. The consequence of this view is that important protective rights of the defendant like the ban of retroactivity in Art. 103 para. 2 of the German Constitution are applicable.